2012
DOI: 10.1037/h0093964
|View full text |Cite
|
Sign up to set email alerts
|

Treating offenders with mental illness: A research synthesis.

Abstract: The purpose of this research synthesis was to examine treatment effects across studies of the service providers to offenders with mental illness. Meta-analytic techniques were applied to 26 empirical studies obtained from a review of 12,154 research documents. Outcomes of interest in this review included measures of both psychiatric and criminal functioning. Although meta-analytic results are based on a small sample of available studies, results suggest interventions with offenders with mental illness effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(88 citation statements)
references
References 93 publications
2
83
0
3
Order By: Relevance
“…The Risk, Need, and Responsivity (RNR) model has been the most widely used and validated model of offender rehabilitation (Andrews & Bonta, 2010Andrews et al, 1990 although its applicability to mentally disordered offenders needs further attention (Morgan et al, 2012). The RNR model outlines the importance of treating criminogenic needs -that is, dynamic offender characteristics, that when changed, are associated with reduced recidivism rates.…”
Section: Discussionmentioning
confidence: 97%
“…The Risk, Need, and Responsivity (RNR) model has been the most widely used and validated model of offender rehabilitation (Andrews & Bonta, 2010Andrews et al, 1990 although its applicability to mentally disordered offenders needs further attention (Morgan et al, 2012). The RNR model outlines the importance of treating criminogenic needs -that is, dynamic offender characteristics, that when changed, are associated with reduced recidivism rates.…”
Section: Discussionmentioning
confidence: 97%
“…Countering this, some researchers have found that for select patients, mental illness can be a factor for recidivism [73][74][75]. This suggest that risk assessment and management is not as simple as applying a quick risk assessment tool; instead a more nuanced approach by appropriately trained medical professionals is necessary.…”
Section: Risk Assessment and Risk Management Of Elderly Sex Offendersmentioning
confidence: 95%
“…In adult forensic populations, as far as we know, no meta-analyses show clear consistent associations between forensic treatment and a reduction in recidivism. In a research synthesis by Morgan et al (2012), treatment effects of service providers to offenders with mental illness were examined across studies. Some studies suggested that forensic interventions can reduce symptoms of distress and improve offender's ability to cope with their problems, resulting in adapted behavioural markers such as institutional adjustment.…”
Section: Introductionmentioning
confidence: 99%